2023
DOI: 10.3389/fpls.2023.1129515
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome and metabolome analyses of cherry leaves spot disease caused by Alternaria alternata

Abstract: Alternaria alternata is a necrotrophic fungal pathogen with a broad host range that causes widespread and devastating disease in sweet cherry (Prunus avium). We selected a resistant cultivar (RC) and a susceptible cultivar (SC) of cherry and used a combined physiological, transcriptomic, and metabolomic approach to investigate the molecular mechanisms underlying the plant’s resistance to A. alternata, of which little is known. We found that A. alternata infection stimulated the outbreak of reactive oxygen spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Plants have evolved various multi-branched phenylalanine metabolism pathways that produce many metabolites, including flavonoids, lignin, lignans, and cassia bark acid amides. In a recent study on cherry, the proteins encoded by CAD , POD , CCoAOMT , 4CL , CCR , and COMT genes were revealed to affect the lignin content, suggestive of their possible role in the resistance to Alternaria alternata [ 32 ]. Lignin can contribute to the scavenging of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have evolved various multi-branched phenylalanine metabolism pathways that produce many metabolites, including flavonoids, lignin, lignans, and cassia bark acid amides. In a recent study on cherry, the proteins encoded by CAD , POD , CCoAOMT , 4CL , CCR , and COMT genes were revealed to affect the lignin content, suggestive of their possible role in the resistance to Alternaria alternata [ 32 ]. Lignin can contribute to the scavenging of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%
“…To respond to fungal attacks, plants produce defense-related compounds and different phytohormones. High-throughput data obtained through liquid chromatography tandem mass spectrometry (LC–MS/MS) and RNA-seq technology can objectively and comprehensively reflect the global metabolic change and transcriptional expression associated with pathogen responses [ 40 ], such as the resistance induced by different elicitors or natural molecules. At present, many studies have shown that exogenously applied elicitors or natural molecules can induce plant defense responses.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput data obtained through liquid chromatography tandem mass spectrometry (LC-MS/MS) and RNA-seq technology can objectively and comprehensively re ect the global metabolic change and transcriptional expression associated with pathogen responses [39], such as the resistance induced by different elicitors or natural molecules. At present, many studies have shown that exogenously applied elicitors or natural molecules can induce plant defense responses.…”
Section: Ja Enhances Resistance To Fungal Pathogen In Plantsmentioning
confidence: 99%